Forensic Odontology-A Review - Prabhu Manickam Natarajan, Asok Mathew2 , Vijay Bhavrao Desai3 , Shibu Thomas4 , Eyas Abuhijleh5 , S (Institute of Medico-legal Publications Pvt Ltd, 2020)
Forensic dentistry may be defined as that branch of forensic medicine that applies dental knowledge tocivil and criminal problems. It is the branch of Forensic sciences which utilizes the skill of the dentist inthe processing, review, evaluation and presentation of dental evidence with the purpose of contributingscientific and objective data in legal processes. The methods of collecting the data utilizes the developedtechnologies and have undergone significant transformation. The methods used include, dental imagingtechniques, bite-mark analysis, DNA analysis using oral tissues, cheiloscopy, and rugoscopy in additionto facial reconstruction, denture identification, comparison microscopes, and tongue prints which are therecent inputs in the field of forensic odontology. This article provides an overview of the recent trends inconventional forensic methods and also provides an insight into the recent concepts used in this field.